The welfare effects of endogenous quality choice in cable television markets - Gregory S. Crawford; Oleksandr Shcherbakov; Matthew Shum (University of Zurich, Department of Economics, 2015)
We measure the welfare consequences of endogenous quality choice in imperfectly competitive markets. We introduce the concept of a "quality markup" and measure the relative welfare consequences of market power over price and quality. For U.S. paid-television markets during 1997-2006, we find that not only are cable monopolists' prices 33% to 74% higher than marginal costs, but qualities are also 23% to 55% higher than socially optimal and the welfare costs of each are similar in magnitude. Such evidence for "quality inflation" by monopolists is at odds with classic results in the literature.
Keywords: L15; L13; L82; L96; C51; 330; industrial organization; endogenous quality; imperfect competition; monopoly; cable television; pay television; welfare; quality markup